Economic Problems of Elderly: A Descriptive Analytical Study in Muscat - Karadsheh, Muneer; Al-Mawali, Nasser (Dirasat: Human and Social Sciences, 2021)
This study aims to reveal the most important economic challenged faced by elderly in Muscat through the measurement of different indicator that are related, in addition to identify the impact of some independent variables on these economic challenges. A descriptive analytical approach was employed in this study and the data collection tool was a questionnaire distributed among 2332 of elderly in Muscat. Results showed that the percentage of elderly who are suffering from financial problem was small and that inability to cover treatment cost was the main economic challenges of them. Results also revealed that women elderly are suffering from economic challenges more than men.